Kinematic and kinetic characteristics exhibit differences in two typical progressive movements of Baduangong and Tai Chi: a comparison based on personalized musculoskeletal simulation analysis - Yang, Peng; Xiao, Boya; Liu, Canwen; He, Qifei; Sun, Weichao; Lv, Yang; Huang, Zexing; Xu, Shuchai; Liu, Yan; Li, Yongjin; Lin, Dingkun; Guo, Da (Frontiers in Bioengineering and Biotechnology, 2026)
PurposeThis study aims to analyze the lower limb kinematic and kinetic characteristics of these two Qigong progressive movements, laying a preliminary biomechanical foundation for exploring their potential applications in targeted movement-based interventions.MethodsA total of 21 non-athletic healthy students were recruited, all of whom had completed Qigong course training. Motion capture equipment was used to collect motion data and ground reaction force data of each participant, including data for 8th movement of Baduangong (BDG (8th)), warding off in advancing of Tai Chi (TC (WOA)), and normal walking gait (NG (Walk)). The AnyBody Modeling System was used for personalization to construct a musculoskeletal model based on the participants’ body weight and fat percentage. Kinematic and inverse dynamics analyses were conducted to obtain lower limb joint range of motion (ROM), joint reaction forces, and moments.ResultsTwo progressive movements had similar gait cycles (9–10 s), longer than NG (Walk) (1.15 ± 0.04 s, p < 0.01), with larger joint ROM (especially hip/knee flexion-extension). Their lower limb joint forces, moments were higher than NG (Walk) (p < 0.05); Comparing the two progressive movements, TC (WOA) exhibited higher peak joint reaction forces (p < 0.05); while BDG (8th) demonstrated greater peak hip abduction and extension moments (p < 0.05).ConclusionThe two progressive movements share the Qigong characteristic of “slowness and continuity”, but they exhibit different biomechanical features due to different movement design concepts. BDG (8th) is characterized by “fast rhythm, long stride length, and flexible transformation”, and exhibits high hip abduction moments. TC(WOA) is characterized by “slow rhythm, short stride length, and phased regulation” and shows kinematic features associated with multi-directional joint movement control. These findings lay a preliminary biomechanical foundation for exploring the potential differentiated applications of the two Qigong movements.